2023
DOI: 10.3389/fmicb.2023.1173614
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome as a potential source of non-invasive biomarkers of chronic obstructive pulmonary disease

Abstract: BackgroundThe link between gut microbial dysbiosis and the development of chronic obstructive pulmonary disease (COPD) is of considerable interest. However, little is known regarding the potential for the use of the fecal metagenome for the diagnosis of COPD.MethodsA total of 80 healthy controls, 31 patients with COPD severity stages I or II, and 49 patients with COPD severity stages III or IV fecal samples were subjected to metagenomic analysis. We characterized the gut microbiome, identified microbial taxono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…8 Chinese mild COPD cohorts had higher abundance of Prevotellaceae while patients with severe disease had lower abundance of Bacteroidaceae and Fusobacteriaceae, 43 and identified that Bacteroides sp CAG875, Christensenella minuta and Clostridium sp Marseille-P2538 were the most abundant species in faeces differentiating healthy donors from patients with COPD. 44 In a Korean cohort, patients with COPD were differentiated from asymptomatic smokers by 17 bacterial groups including lower Prevotella copri, Dialister succinatiphilus and Catenibacterium mitsuokai and increased Bacteroides fragilis and Bifidobacterium longum, 45 highlighting the challenges of identifying a consistent microbial marker of disease especially given the demographic differences between cohorts. Some studies in mice have identified that CS-exposure increased Lachnospiraceae abundance, 11 while others report decreases.…”
Section: Discussionmentioning
confidence: 99%
“…8 Chinese mild COPD cohorts had higher abundance of Prevotellaceae while patients with severe disease had lower abundance of Bacteroidaceae and Fusobacteriaceae, 43 and identified that Bacteroides sp CAG875, Christensenella minuta and Clostridium sp Marseille-P2538 were the most abundant species in faeces differentiating healthy donors from patients with COPD. 44 In a Korean cohort, patients with COPD were differentiated from asymptomatic smokers by 17 bacterial groups including lower Prevotella copri, Dialister succinatiphilus and Catenibacterium mitsuokai and increased Bacteroides fragilis and Bifidobacterium longum, 45 highlighting the challenges of identifying a consistent microbial marker of disease especially given the demographic differences between cohorts. Some studies in mice have identified that CS-exposure increased Lachnospiraceae abundance, 11 while others report decreases.…”
Section: Discussionmentioning
confidence: 99%
“…As a whole, we report new data supporting important NLRP6 functions in basal and pathological lung settings that could be translated to a clinical setting following preclinical validations. Gut microbiota-derived metabolites or components might represent biomarkers present in the blood of COPD patients ( 43 , 71 ). In addition, this study uncovers NLRP6 as a new target for the development of potential therapeutic strategies against COPD by specific inhibition of NLRP6.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, integrating the oral–lung axis as a single niche with inter‐connected microenvironments may take multi‐omics microbiome studies into a next level, towards establishing more robust clinically meaningful interactions between exposure, microbial dysbiosis and disease outcomes. Going further, functional associations between oral–lung dysbiosis and respiratory dysfunction could be expanded towards a more comprehensive view by integrating links between gut microbiota dysbiosis and airway disease into the equation, as gut dysbiosis is another well‐known microbiome contributor of COPD development (Li et al., 2021 ; Li, Wang, et al., 2023 ; Li, Yi, et al., 2023 ; Wang et al., 2023 ) (Figure 1 , lower left panels).…”
Section: Challenges and Opportunities Of The Oral–lung Axis Microbiom...mentioning
confidence: 99%